Novel marine actinobacteria from emerald Andaman & Nicobar Islands: a prospective source for industrial and pharmaceutical byproducts - Meena, Balakrishnan (BioMed Central, 2013)
BACKGROUND: Andaman and Nicobar Islands situated in the eastern part of Bay of Bengal are one of the distinguished biodiversity hotspot. Even though number of studies carried out on the marine flora and fauna, the studies on actinobacteria from Andaman and Nicobar Islands are meager. The aim of the present study was to screen the actinobacteria for their characterization and identify the potential sources for industrial and pharmaceutical byproducts. RESULTS: A total of 26 actinobacterial strains were isolated from the marine sediments collected from various sites of Port Blair Bay where no collection has been characterized previously. Isolates were categorized under the genera: Saccharopolyspora, Streptomyces, Nocardiopsis, Streptoverticillium, Microtetraspora, Actinopolyspora, Actinokineospora and Dactylosporangium. Majority of the isolates were found to produce industrially important enzymes such as amylase, protease, gelatinase, lipase, DNase, cellulase, urease and phosphatase, and also exhibited substantial antibacterial activity against human pathogens. 77% of isolates exhibited significant hemolytic activity. Among 26 isolates, three strains (NIOT-VKKMA02, NIOT-VKKMA22 and NIOT-VKKMA26) were found to generate appreciable extent of surfactant, amylase, cellulase and protease enzyme. NIOT-VKKMA02 produced surfactant using kerosene as carbon source and emulsified upto E(24)–63.6%. Moreover, NIOT-VKKMA02, NIOT-VKKMA22 and NIOT-VKKMA26 synthesized 13.27 U/ml, 9.85 U/ml and 8.03 U/ml amylase; 7.75 U/ml, 5.01 U/ml and 2.08 U/ml of cellulase and 11.34 U/ml, 6.89 U/ml and 3.51 U/ml of protease enzyme, respectively. CONCLUSIONS: High diversity of marine actinobacteria was isolated and characterized in this work including undescribed species and species not previously reported from emerald Andaman and Nicobar Islands, including Streptomyces griseus, Streptomyces venezuelae and Saccharopolyspora salina. The enhanced salt, pH and temperature tolerance of the actinobacterial isolates along with their capacity to secrete commercially valuable primary and secondary metabolites emerges as an attractive feature of these organisms. These results are reported for the first time from these emerald Islands and expand the scope to functionally characterize novel marine actinobacteria and their metabolites for the potential novel molecules of commercial interest.